Value of c-Met for Predicting Progression of Precancerous Gastric Lesions in Rural Chinese Population - Sun, Yu; Tian, Meng-meng; Zhou, Li-xin; You, Wei-cheng; Li, Ji-you (Chinese journal of cancer research, 2012)
Objective： To investigate the value of c-Met in predicting progression of precancerous gastric lesions. Methods： A population-based study was conducted to detect the overexpression of c-Met by immunohisto- chemical analysis in 124 subjects with precancerous gastric lesions. Odds ratio （OR） and 95% confidence interval （95% CI） were calculated for the association of c-Met overexpression with the risk of advanced gastric lesions. Results： The positive rates of c-Met were 55.7% in intestinal metaplasia （IM） and 64.8% in dysplasia （DYS）, respectively. Stratified analysis indicated that the proportion of c-Met overexpression was 71.4% for IM progressive group, significantly higher than that for IM persistent group （40.0%, P〈O.05）. Compared to the IM persistent group, unconditional logistic regression showed that OR of c-Met overexpression for the IM progressive group was 7.426 （95% Cl： 2.084-26.398）. Conclusion： c-Met plays an important role in gastric carcinogenesis. Detection of c-Met is of value in predicting progression of precancerous gastric lesions from IM to DYS.